Gas sensing and electrochemical properties of tetra and octa 2H-chromen-2-one substituted iron(II) phthalocyanines - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN; ALTUN, SELÇUK; ODABAŞ, ZAFER (ROYAL SOC CHEMISTRY, 2015)
The synthesis of novel alpha tetra, beta tetra and beta octa 4-(4-methoxyphenyl)-8-methyl-coumarin-7-oxy, and beta octa 4-chloro-5-(4-(4-methoxyphenyl)-8-methylcoumarin-7-oxy) substituted iron(II) phthalocyanines has been achieved by the reaction of the corresponding phthalonitriles with iron(II) acetate. The compounds were characterized by elemental analysis, FT-IR, UV-vis, and MALDI-TOF mass spectrometry. The reduction and oxidation properties of the compounds were identified by voltammetric and in situ spectroelectrochemical measurements. The gas sensing behavior of the spin coated films of the differently substituted iron(II) complexes towards CO2, CO and SO2 was investigated at various temperatures between 300 K and 500 K. While exposure to SO2 had no considerable influence on the sensor current, the presence of CO and CO2 gases led to a large increase in sensor currents. The effect of relative humidity on the CO and CO2 sensing capability of the spin coated films was also studied. The results showed that the presence of water vapor, acting as an interference gas, causes a decrease in the CO2 sensitivity, but an increase in the CO sensitivity of the sensors. The experimental adsorption data were analyzed using the Elovich kinetic model. Linear regression analysis results show that the Elovich equation provides the best correlation for the CO2 and CO adsorption processes under humid conditions. However, the experimental data deviated considerably from the theoretical model under a dry atmosphere.
Keywords: THIN-FILM; ZINC PHTHALOCYANINES; METAL-FREE; CATALYZED OXIDATION; OXYGEN REDUCTION; METALLOPHTHALOCYANINES; COUMARIN; KINETICS; TRANSISTORS; ADSORPTION